Influência da razão coroa/implante e da espessura de osso cortical nas tensões em osso peri-implantar e componentes protéticos : uma análise de elementos finitos - Baldisserotto, Simone Michielon (2021)
The mandible posterior regions generally have bone height limitations. Short implant is one of the treatment options and it has been used widely due to technical and clinical simplification. However, the treatment predictability is related to several biomechanical factors, such as crown/ implant ratio, periimplant tissues integrity and masticatory forces distribution over implants and components. The aim of this study was to evaluate the stress distribution on the prosthetic components of short implant supporting single crowns and peri-implant bone, in the posterior mandible, as a function of two combinations of cortical bone thicknesses and crown-to-implant ratio (C/I)., when exposed to vertical and oblique forces. Methodology: This study used a finite element non-linear analysis method. Two virtual models of the posterior edentulous jaw region were created with 1.0 mm and 2.0 mm cortical bone thicknesses. A 6 mm and 4.1mm diameter implants were loaded by unitary fixed prostheses with different C / I ratios (1.6 and 2.25). Simulation loads of 100N were applied axial and oblique (15 °). The principal stress theory and von Mises were used. The results were described in displacement maps, for quantitative and qualitative analysis. Results: Both, the C / I ratio and the cortical bone thickness affected the magnitude and stress distribution in peri-implant bone and prosthetic components under different directions of occlusal loads. An increase in C / I ratio and cortical bone thickness directed the concentration of von Mises stresses to the region near the marginal ridge. In a quantitative analysis, the screws received more loads when oblique forces were applied, mainly in 2-mm cortical bone and higher C / I ratio. Conclusions: Both the C / I ratio and the thickness of the cortical bone affected the magnitude and stress distribution in the peri-implant bone and prosthetic components. The biomechanics studies of single tooth rehabilitation with short implants are important for extrapolations of conventional prosthesis principles around the natural dentition do not guide implant-supported rehabilitation.